Effect of In Diffusion on the Property of Blue Light-Emitting Diodes - 曾勇平 刘文杰 翁国恩 赵婉茹 左海杰 余健 张江勇 应磊莹 张保平 (Chinese physics letters, 2015)
In diffusion to blue light-emitting diode （LED） wafers is performed by the inductive coupled plasma （ICP） treatment of a covering layer of indium tin oxide （ITO） on the wafer surface. The electrical property of the p- type contact is improved and the redshift of photoluminescence （PL） from the InGaN quantum well of the wafer is found. Measurements by x-ray photoelectron spectroscopy （XPS） demonstrate that In atoms have diffused into p-GaN. Reflectance spectra of the sample surface reveal the variation caused by the ICP treatment. A model of compensation of the in-plane strain of the InGaN layer is used to explain the redshift of the PL data. Finally, LEDs are fabricated by using as-grown and ICP-treated wafers and their properties are compared. Under an injection current of 20mA, LEDs with ICP-induced In doping show a decrease of 0.3 V in the forward voltage and an increase of 23% in the light output, respectively.